Extrahepatic Portal Vein Obstruction in Egyptian Children. Issue 1 (January 2015) - El-Karaksy, Hanaa M.; El-Koofy, Nehal; Mohsen, Nabil; Helmy, Heba; Nabil, Nevian; El-Shabrawi, Mortada
ABSTRACT: Background and Aim: Extrahepatic portal vein obstruction (EHPVO) is an important cause of portal hypertension in children. The aim of this study was to describe the clinical presentation, possible risk factors, upper gastrointestinal endoscopic findings, and treatment modalities of children with EHPVO. Methods: After ethical approval of our study protocol by our institution review board, we analyzed available data from medical records of patients with EHPVO presenting to the Pediatric Hepatology Unit, Cairo University Pediatric Hospital, Egypt, for a period of 15 years from January 1996 to December 2010. Results: The study included 169 patients. Their ages at presentation ranged from 1 month to 12 years (median 2.5 years, interquartile range 5); 101 were boys. Hematemesis was a presenting symptom in 58%, splenomegaly was present in 87%, esophageal varices were present in 94%, and fundal varices were present in 23%. Possible risk factors, in the form of umbilical catheterization, umbilical sepsis, and exchange transfusion, were elicited in 18%. Propranolol was associated with reduction in bleeding episodes ( P  < 0.001), but was associated with increased chest symptoms ( P  < 0.01). Both injection sclerotherapy and band ligation were effective in the management of bleeding varices and for primary and secondary prophylaxis; however, injection sclerotherapy was associated with the development of secondary gastric varices ( P  = 0.03). Conclusions: This large study of children with EHPVO demonstrates the efficacy of propranolol in the reduction of gastrointestinal bleeding in children with EHPVO. Both injection sclerotherapy and band ligation were effective in the management of esophageal varices, although the former was associated with the development of secondary gastric varices. Randomized clinical trials to choose the best modalities for the management of portal hypertension in children are still lacking.